1987
DOI: 10.1203/00006450-198706000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin Does Not Alter the Circulating Catecholamine Response to Asphyxia in the Neonatal Piglet

Abstract: ABSTRACT. The response of circulating catecholamines to asphyxia in unanesthetized, spontaneously breathing neonatal piglets was measured before and after treatment with indomethacin. Prior to treatment with indomethacin, baseline levels [geometric mean, pg/ml (95% confidence limits)] of D, E, and N were 162 (99-266), 174 (52-579), and 380 (286-506), respectively. Inhalation of 10% 02/9% CO? for 20 min caused significant increases in arterial levels of all three catecholamines to 389 (230-659, 1514 (993-2306)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…; Green et al . ). Furthermore, any possible affect of INDO on the peripheral chemoreceptors is unlikely.…”
Section: Discussionmentioning
confidence: 97%
“…; Green et al . ). Furthermore, any possible affect of INDO on the peripheral chemoreceptors is unlikely.…”
Section: Discussionmentioning
confidence: 97%
“…Indomethacin was used in this study as a pharmacological means to reduce cerebrovascular CO 2 reactivity in healthy resting humans without concomitant changes in cerebral metabolic rate (Hohimer et al 1985;Kraaier et al 1992) or plasma catecholamine concentrations (Green et al 1987;Staessen et al 1984;Wennmalm et al 1984). Studies have shown that the peak effect of INDO (100 mg) on reducing MCAv occurs at *90 min and persists for [4 h following ingestion (Markus et al 1994;Xie et al 2006).…”
Section: Indomethacinmentioning
confidence: 97%
“…Accordingly, the authors concluded that INDO lowers CBF and cerebrovascular CO 2 reactivity by selective inhibition of prostaglandin H synthase and prostacyclin receptor-mediated responses (Parfenova et al 1995b). Moreover, numerous studies have found that INDO lowers CBF and attenuates the cerebrovascular reactivity to CO 2 (Bruhn et al 2001;Eriksson et al 1983;Ivancev et al 2009;Kastrup et al 1999;Markus et al 1994;St Lawrence et al 2002;Wennmalm et al 1983) without concomitant changes in cerebral metabolic rate (Hohimer et al 1985;Kraaier et al 1992) or plasma catecholamines (Green et al 1987;Staessen et al 1984;Wennmalm et al 1984).…”
Section: Introductionmentioning
confidence: 93%
“…Indomethacin (INDO) is a potent reversible cyclooxygenase inhibitor that blocks prostaglandin production in the cerebrovasculature, thereby decreasing CBF and attenuating the cerebrovascular CO 2 reactivity (6,17,36,53) without concomitant changes in metabolic rate (26,35) or plasma catecholamines (25,54,58). This unique feature makes INDO an ideal tool for investigating the role of cerebrovascular CO 2 reactivity in the control of breathing in humans.…”
mentioning
confidence: 99%